Penyusunan Kriteria Pemilihan Proses Flue Gas Desulfurization PLTU-Batubara - Herri Santoso (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Approximately 42% (29 GWh/year) of electricity in Indonesia is produced from coal-fired power plants with coal consumption of about 45 million ton/year. Anticipating the increase in coal consumption for fuel in power plants and industries, as well as the decrease in coal quality in terms of heating value and sulfur content, application of flue gas desulfurization (FGD) will be a mandatory in the near future. Characteristics of several FGD technologies are shortly discussed in this paper. Based on this study the criteria for the selection are as follows: capacity and location of the power plant, concentration of SO2in flue gas and specific emissions of SO2 which depends on coal quality, separation efficiency, chemicals requirement and by-product, reliablity and commercial status of technology, and of course investment, operating and maintenance costs. These criteria will be used in the Analytic Hierarchy Process to determine a suitable technology for a particular coal power plant.